Vaccinia Virus Activation and Antagonism of Cytosolic DNA Sensing - El-Jesr, Misbah; Teir, Muad; Maluquer de Motes, Carlos (Frontiers in Immunology, 2020)
Cells express multiple molecules aimed at detecting incoming virus and infection. Recognition of virus infection leads to the production of cytokines, chemokines and restriction factors that limit virus replication and activate an adaptive immune response offering long-term protection. Recognition of cytosolic DNA has become a central immune sensing mechanism involved in infection, autoinflammation and cancer immunotherapy. Vaccinia virus (VACV) is the prototypic member of the family Poxviridae and the vaccine used to eradicate smallpox. VACV harbours enormous potential as a vaccine vector and several attenuated strains are currently being developed against infectious diseases. In addition, VACV has emerged as a popular oncolytic agent due to its cytotoxic capacity even in hypoxic environments. As a poxvirus, VACV is an unusual virus that replicates its large DNA genome exclusively in the cytoplasm of infected cells. Despite producing large amounts of cytosolic DNA, VACV efficiently suppresses the subsequent innate immune response by deploying an arsenal of proteins with capacity to disable host antiviral signalling, some of which specifically target cytosolic DNA sensing pathways. Some of these strategies are conserved amongst orthopoxviruses, whereas others are seemingly unique to VACV. In this review we provide an overview of the VACV replicative cycle and discuss the recent advances on our understanding of how VACV induces and antagonises innate immune activation via cytosolic DNA sensing pathways. The implications of these findings in the rational design of vaccines and oncolytics based on VACV are also discussed.